The Influence of Service Quality and Price on J&T Express Customer Loyalty in Medan City (Study at Setia Budi Medan Branch) - Anggi Lisnadianti (Cattleya Darmaya Fortuna, 2022)
The development of online commerce has given birth to a new shopping model. This has led to the emergence of new businesses seeking more delivery orders. E-Commerce business actors use direct shipping services as a shipping method. Delivery services have an important role for e-commerce in achieving market success and growth because consumers and customers want to get their goods quickly, an effective service quality system and affordable shipping prices. This study aims to analyze and determine the effect of service quality and price on customer loyalty J&T Express in the city of Medan (J&T Express Setia Budi Medan). This study was conducted to determine how much influence the quality of service and price on customer loyalty J&T Express in the city of Medan (J&T Express Setia Budi Medan). This study uses a quantitative method with an associative approach. The data analysis method used is instrument test through validity and reliability test, classical assumption test, multiple regression analysis test, hypothesis test through t-test and F-test, and coefficient of determination test. Tests were carried out using SPSS V.22. The results showed that the service quality variable had a significant effect on customer loyalty J&T Express in Medan City (J&T Express Setia Budi Medan). The price variable has no effect on customer loyalty at J&T Express in Medan City (J&T Express Setia Budi Medan). Simultaneously the quality of service and price affect the loyalty of J&T Express customers in the city of Medan (J&T Express Setia Budi Medan). The data analysis method used is instrument test through validity and reliability test, classical assumption test, multiple regression analysis test, hypothesis test through t-test and F-test, and coefficient of determination test. Tests were carried out using SPSS V.22. The results showed that the service quality variable had a significant effect on customer loyalty J&T Express in Medan City (J&T Express Setia Budi Medan). The price variable has no effect on customer loyalty at J&T Express in Medan City (J&T Express Setia Budi Medan). Simultaneously the quality of service and price affect the loyalty of J&T Express customers in the city of Medan (J&T Express Setia Budi Medan). The data analysis method used is instrument test through validity and reliability test, classical assumption test, multiple regression analysis test, hypothesis test through t-test and F-test, and coefficient of determination test. Tests were carried out using SPSS V.22. The results showed that the service quality variable had a significant effect on customer loyalty J&T Express in Medan City (J&T Express Setia Budi Medan). The price variable has no effect on customer loyalty at J&T Express in Medan City (J&T Express Setia Budi Medan). Simultaneously the quality of service and price affect the loyalty of J&T Express customers in the city of Medan (J&T Express Setia Budi Medan). and coefficient of determination test. Tests were carried out using SPSS V.22. The results showed that the service quality variable had a significant effect on customer loyalty J&T Express in Medan City (J&T Express Setia Budi Medan). The price variable has no effect on customer loyalty at J&T Express in Medan City (J&T Express Setia Budi Medan). Simultaneously the quality of service and price affect the loyalty of J&T Express customers in the city of Medan (J&T Express Setia Budi Medan). and coefficient of determination test. Tests were carried out using SPSS V.22. The results showed that the service quality variable had a significant effect on customer loyalty J&T Express in Medan City (J&T Express Setia Budi Medan). The price variable has no effect on customer loyalty at J&T Express in Medan City (J&T Express Setia Budi Medan). Simultaneously the quality of service and price affect the loyalty of J&T Express customers in the city of Medan (J&T Express Setia Budi Medan). T Express Setia Budi Medan). Simultaneously the quality of service and price affect the loyalty of J&T Express customers in the city of Medan (J&T Express Setia Budi Medan). T Express Setia Budi Medan). Simultaneously the quality of service and price affect the loyalty of J&T Express customers in the city of Medan (J&T Express Setia Budi Medan).